Utilization of Environmentally Friendly Energy in Organic Fertilizer Processing Machine - Yendi Esye; Husen Asbanu; Danny Faturachman; Yefri Chan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Agriculture is the primary livelihood for most of Indonesia's population, which has vast agricultural land. However, there remains a dependency on chemical fertilizers, which degrade soil quality compared to organic farming that can optimize plant health and productivity. The energy needs in the agricultural sector, including mechanization and fertilizer production, are critical but still heavily reliant on fossil fuels. It is, therefore, essential to reduce this dependency by utilizing environmentally friendly alternative energy sources. This study examines the use of solar energy to power machines in the process of producing organic fertilizer. The tools used in the study include a 100 Wp solar panel, solar energy conversion components, a 12 Volt 33 Ah battery, a ¼ Hp electric motor, a voltage and current meter, a temperature gauge, a sunlight intensity meter, and an organic fertilizer processing machine. The research method analyzes several variables, including sunlight intensity, power, voltage, current, charging time, and battery usage. The study found that the solar panel used was insufficient to power the ¼ HP motor, requiring the addition of three more solar panels and batteries to meet the motor's power requirement of 233 watts. Battery charging tests required 3 hours, and battery usage for machine operation without solar panel installation lasted 1 hour and 40 minutes, while battery usage for machine operation with solar panel installation lasted 6-7 hours. Keywords: Environmentally friendly energy, Fertilizer crushing machine, Organic fertilizer, Solar energy.